Problematika Pembelajaran Bahasa Arab pada Siswa Kelas VIII Madrasah Tsanawiyah - Mahsya Agniya Hanifa; Moch. Hasyim Fanirin; Moh. Mas’ud Arifin (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This article aims to explain the problems faced by students in learning Arabic and the efforts made to overcome the problems of learning Arabic at Madrasah Tsanawiyah Ma'had Al-Zaytun. This article uses a qualitative method with interview techniques to the head of the madrasah, class VIII language teachers, and 54 class VIII students, conducting observations, distributing questionnaires, and documentation. The results of the study showed that the problems of learning Arabic: Problems of interest in learning, with the lowest percentage of interest indicators being feelings of pleasure (46%). Problems of language environment, with the lowest percentage of environmental indicators being auditory and visual environments (44%). Problems of support for learning Arabic, with the lowest percentage of support indicators being emotional support and appreciation (51%). And the efforts made by teachers in increasing interest in learning Arabic are using the quantum method, creating a comfortable and effective teaching and learning atmosphere, efforts to create an Arabic language environment: creating a zoning program in the Arabic language laboratory and the use of Arabic language labels, the school creates a hijaiyah literacy free program, makes policies in creating a language environment and efforts to increase support: teachers provide support and encouragement by encouraging students, and directing students to participate in extracurricular activities.